Exploring the Involvement of New Members of the Interleukin Family in Cardiovascular Disease - Al Noman, Abdullah; Flora, Sanzida Alam; Datta, Monty; Afrose, Fahmida; Hasan, Nushaiba Binte; Akhter, Tahamina; Anuva, Nayeema Jameel; Pathak, Rashmi; Sharma, Himanshu (Current Cardiology Reviews, 2025)
Cardiovascular diseases remain a significant reason for illness and death globally. Although certain interleukins have been extensively researched about cardiovascular disease (CVD), new findings have identified unique members of the interleukin family that could potentially play a role in cardiovascular well-being and ailments. This review discusses the current understanding of the role of these recently identified interleukins, such as IL-27, IL-31, IL-32, IL-33, and the IL-28 group (IL-28A, IL-28B, IL-29), in the development of cardiovascular diseases. Every interleukin has various impacts achieved through particular receptors and signaling pathways that affect inflammatory processes, differentiation of immune cells, and the functioning of blood vessels. IL-27 controls the development of inflammatory Th17 cells and might decrease inflammation in atherosclerosis. IL-31 plays a role in the interaction between the immune system and nerves, as well as in itching. IL-32 enhances the generation of inflammatory proteins and has been linked to coronary artery disease. IL-33 has beneficial effects on the cardiovascular system, whereas its imitation receptor sST2 could potentially be used as a biomarker. Additional studies are needed to investigate the antiviral and immune-system regulating effects of the IL-28 group in cardiovascular diseases. In general, explaining the ways in which new interleukins contribute to the progression of cardiovascular diseases can help discover fresh targets for therapy and new approaches toward enhancing the prevention and treatment of heart disorders. Additional research on the way these cytokines engage with established disease pathways is necessary.
Keywords: interleukin